LAND SUITABILITY ANALYSIS FOR RICE CULTIVATION IN SUNGAI RAYA DISTRICT - Azuryan, Azuryan; Permana, Mohamad Syahriza; Titi, Titi; Julianda, Syarifah; Khoir, Muhammad Thoriqul; Anasi, Putri Tipa; Christanto, Ludovicus Manditya Hari (Universitas Tanjungpura, 2025)
This study aims to analyze the level of suitability of rice farming land in Sungai Raya District, Kubu Raya Regency, West Kalimantan. The research method uses a descriptive quantitative approach with a spatial overlay analysis technique based on Geographic Information Systems (GIS). The parameters analyzed include physical environmental factors in the form of temperature (24-32 °C), soil texture (fine and medium), soil depth (>50 cm), soil pH (4.5-8.2), soil drainage, cation exchange capacity (CEC), and slope (0-15%). Secondary data were obtained from various institutions related to the observation years 2017-2023. The results of the study indicate that Sungai Raya District has great potential for the development of rice farming with a dominant classification of suitable (S2) covering an area of 92,457 hectares and marginally suitable (S3) covering an area of 19,451 hectares. The actual utilization of rice fields currently only reaches 24,614 hectares (S2) and 4,493 hectares (S3), which means that only 26.6% of S2 land and 23% of S3 land have been utilized. This study shows that there is still a great opportunity for extensification and intensification of rice farming in the region to support regional food security.